2007
DOI: 10.1007/s11274-007-9504-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipases catalyzed enantioselective hydrolysis of (R,S)-methyl 1,4-benzodioxan-2-carboxylate intermediate for (S)-doxazosin mesylate

Abstract: S)-1,4-benzodioxan-2-carboxylic acid-1 is used as starting compound for the production of the more effective (S) enantiomer of the drug doxazosin mesylate. The catalytic ability of some commercial lipases for preparations of (S) enantiomer of 1 from (±) methyl 1,4-benzodioxin-2-carboxylate-2 is reported. Lipases from bacterial sources were more successful in resolving the ester than those from the yeast lipases. About 85% enantiomerically pure ester was achieved by lipase from alcaligenes sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The metabolic pathway for biosynthesis of kojic acid is still under investigation. It has been reported that an initial enzymatic conversion from glucose to glucosone by pyranose oxidase and catalase in the presence of oxygen, followed by acetylation and deacetylation yield kojic acid [31] …”
Section: Resultsmentioning
confidence: 99%
“…The metabolic pathway for biosynthesis of kojic acid is still under investigation. It has been reported that an initial enzymatic conversion from glucose to glucosone by pyranose oxidase and catalase in the presence of oxygen, followed by acetylation and deacetylation yield kojic acid [31] …”
Section: Resultsmentioning
confidence: 99%
“…This novel feature was demonstrated by employing Amano Lipase PS-C1 (lipase from Burkholdera cepacia immobilized on ceramic beads) in a DKR with 5 mol % of Pd-AmP-MCF which afforded 2a in a good isolated yield and excellent ee (entry 4) . This enzyme has previously been used in the kinetic resolution of 1a , but to the best of our knowledge, this is the first example of a DKR of amines using this biocatalyst …”
Section: Resultsmentioning
confidence: 99%
“…16 This enzyme has previously been used in the kinetic resolution of 1a, but to the best of our knowledge, this is the first example of a DKR of amines using this biocatalyst. 17 After we established the optimized protocols for the DKR at 70 and 50 °C, a set of substrates were studied in the reaction at 70 °C (Table 3). Four benzylic amines substituted with aliphatic substituents were chosen, and were all converted into their corresponding enantiomerically enriched amides in high yields as well as excellent ee's (2a−d).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Among them, optimal results were achieved via enzymatic resolutions of racemic 1,4‐benzodioxan‐2‐carboxylic acid or esters or by diastereomeric crystallization with the (+)‐dehydroabietylamine …”
Section: Introductionmentioning
confidence: 99%
“…Among them, optimal results were achieved via enzymatic resolutions of racemic 1,4-benzodioxan-2carboxylic acid or esters [20][21][22][23][24] or by diastereomeric crystallization with the (+)-dehydroabietylamine. 25 Pondering either yields and commercial availability, we followed the previously defined satisfactory method, in which the 1,4-benzodioxan-2-carboxylic acid was firstly resolved with the chiral dehydroabietylamine acetate and then converted into the methyl ester, affording crystallized (S)-II with high yield and high enantiomeric excess.…”
Section: Introductionmentioning
confidence: 99%